Implementation of Rights and Obligations for Employment Insurance Protection for Private Sector Employees - Salsa Aprilia Aji; Alvi Brian Harda Saputra (Al-Hukumah: Jurnal Ilmu Pemerintahan dan Studi Islam, 2026)
This study analyzes the implementation of labor protection rights and obligations for private sector employees in Indonesia, focusing on regulatory enforcement, factors influencing implementation effectiveness, and the impact on workers’ welfare. Although the regulatory framework has undergone significant updates through the Job Creation Law, and BPJS Employment coverage has reached 43.5 million workers with managed funds totaling IDR 776.8 trillion, there remains a substantial gap at the implementation level. Coverage currently accounts for only 47.91% of the total labor force, and merely 40.85% of laid-off workers successfully access the Unemployment Insurance scheme. Key challenges include weaknesses in digital administrative systems, low employer compliance and awareness, limited worker literacy regarding their rights, and inadequate supervision and enforcement of sanctions. This study highlights the need for a holistic approach integrating regulatory strengthening, enhancement of digital system capacity, intensified monitoring, and expansion of educational programs to optimize labor protection in Indonesia.